A cephalometric study in children from Medellín aged 3 to 6 years with class I dental occlusion - Gómez-Gómez, Julia Andrea; Llano-Sánchez, Elizabeth; Londoño-Urrego, Claudia Patricia; Rendón-Ocampo, Alejandra María; Gaviria-Molina, Mónica María (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: the few available studies that have been done with digital lateral cephalic x-rays in children younger than 6 years makes it necessary to conduct research on this age group. The purpose of this study was to determine the average cephalometric measures in children from the municipality of Medellín aged 3 to 6 years with class I dental occlusion, by estimating differences by age, sex, facial biotype, weight and size. Methods: this was a descriptive transversal study using digital lateral cephalic radiographs in 99 children aged 3 to 6 years who met the inclusion criteria in order to determine cephalometric averages. Results: between the ages of 3 and 4 years there is more sexual dimorphism, with more protrusive maxilla and mandible in girls; these differences are lower at the age of 5, becoming undetectable at the age of 6. The behavior of variables by age show that longitudinal measures tend to increase with age. Dolichofacial kids showed higher values in the anterior-posterior direction of linear measures, while leptofacial kids showed higher values in the angular measures in the vertical direction. There were no statistically significant differences in terms of weight/height relationship with cephalometric variables. Conclusions: the value of linear measures rises as age increases, supporting the use of specific standards for each age. This study suggests that there is sexual dimorphism among cephalometric variables, being more evident at the age of 3 and 4 years. The different facial biotypes show specific cephalometric features.